SCIENCE AND TECHNPOLOGY PARK (STP): TRANSFORMATION TO QUADRUPLE HELIX APPROACH FOR HABITUATION OF SCIENCE AND TECHNOLOGY IN INDONESIA - Ardanareswari Ayu Pitaloka; Muhammad Alie Humaedi (Jurnal Sosioteknologi, 2020)
Science and Technology Park (STP) development is one of science and technology policy implementations that aims to encourage national competitiveness. In the National Medium Term Development Plan (RPJMN) 2015-2019, the Indonesian government has declared the establishment of 100 STPs in 2019. However, in reality, only 22 STPs that have the greatest chance of being completed, even though those STPs have not reached the targeted conditions like STPs in developed countries that successfully increased the economy. This study aims to answer how STP can habituate the culture of science and technology in the community in Indonesia and reveal STP development phenomena in the regional context in Indonesia and other countries. This study found that the various challenges in developing STP will continue to hamper Indonesia if still use triple helix approach, and encourage quadruple helix approach that is able to habituate community for science and technology culture so that its existence and function can be suitable with Indonesian society ecosystem.keywords: STP, Habituation of  Science and Technology, Quadruple Helix.